Circularly polarized luminescent self‐organized helical superstructures: From materials and stimulus‐responsiveness to applications. Issue 6 (22nd October 2021) - He, Yanrong; Lin, Siyang; Guo, Jinbao; Li, Quan
Abstract: Circularly polarized luminescence (CPL) has gained considerable attention in various systems and has rapidly developed into an emerging research field. To meet the needs of actual applications in diverse fields, a high luminescence dissymmetry factor ( g lum ) and tunable optical performance of CPL would be the most urgent pursuit for researchers. Accordingly, many emerging CPL materials and various strategies have been developed to address these critical issues. Emissive cholesteric liquid crystals (CLCs), that is, luminescent self‐organized helical superstructures, are considered to be ideal candidates for constructing CPL‐active materials, as they not only exhibit high g lum values, but also enable flexible optical control of CPL. This review mainly summarizes the characteristics of CPL based on CLCs as the bulk phase doped with different emitters, including aggregated induced emission molecules, conventional organic small molecules, polymer emitters, metal–organic complex emitters, and luminescent nanoparticles. In addition, the recent significant progress in stimulus‐responsive CPL based on emissive CLCs in terms of several types of stimuli, including light, electricity, temperature, mechanical force, and multiple stimuli is presented. Finally, a short perspective on the opportunities and challenges associated with CPL‐active materials based on the CLC field is provided. This review is anticipated to offer new insights and guidelines for developing CLC‐based CPL‐active materials for broader applications. Abstract : Cholesteric liquid crystals (CLCs) with self‐organized helical superstructures have exhibited considerable advantages in terms of achieving high luminescence dissymmetry factors and tunable circularly polarized luminescence (CPL) properties. This review highlights the recent developments in CLC‐based CPL‐active materials doped with various emitters. In addition, stimulus‐responsive CPL based on emissive CLCs is systematically summarized.